2013
DOI: 10.1159/000350243
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Complications of Pneumatic Lithotripsy for the Treatment of Ureteral Stones with Different Localizations: A Multivariate Analysis of Complications

Abstract: Objective: To evaluate the complications of ureterorenoscopy (URS) using the modified Clavien classification system for ureteral stones with different localizations. Patients and Methods: From February 2001 to January 2010, a total of 1,926 patients underwent URS for the treatment of ureteral stones with different localizations. The complications were evaluated according to the modified Clavien system. Univariate and multivariate analyses were conducted to identify risk factors affecting the complication rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…We report an overall SFR of 94.2% after URS treatment at follow-up, a rate similar to previous studies [ 20 ] and a day-case SFR of 95.4%. We did not find a correlation between LoS and SFR, with both the day-case and prolonged admission groups producing excellent SFRs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We report an overall SFR of 94.2% after URS treatment at follow-up, a rate similar to previous studies [ 20 ] and a day-case SFR of 95.4%. We did not find a correlation between LoS and SFR, with both the day-case and prolonged admission groups producing excellent SFRs.…”
Section: Discussionsupporting
confidence: 90%
“…Higher mean pre-operative serum creatinine and longer mean overall stone length were highest in the prolonged stay group (>3 days). With regards to stone parameters, previous studies have reported stone number and stone burden to be associated with higher complication rates post-procedure and this might partly explain our findings [ 19 , 20 ]. In addition, we found that deployment of an access sheath was highest in the group with prolonged stay suggesting a more complex and larger nature of these stones.…”
Section: Discussionmentioning
confidence: 63%
“…Although URS is a more invasive option than SWL, it has a better success rate with an overall success rate extending from 85.6%[ 14 ] to 95.7%. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…They found that stone area is one of the key risk factors affecting URS success (OR = 0.993, p = 0.002). For analysis of negative outcomes, Gunlusoy et al 18 showed stone diameter was a significant parameter for the occurrence of complications (relative risk of 2 in multivariate analysis). However, we found conflicting evidence in a previous study that stone clearance is not affected by stone size.…”
Section: Discussionmentioning
confidence: 99%